Radioiodine Thyroid Uptake and Scintigraphy in the Evaluation of Hyperthyroidism with Multinodular Goiter - Islam, M. R.; Islam, F. N.; Haque, M. M.; Hossain, M. S.; Reza, M. S.; Begum, R. (Journal of Scientific Research, 2018)
The role of radioactive iodine uptake and scintigraphy were studied over 111 subjects with a mean age of 42±13 years, 65% females and 35% males, in the evaluation of hyperthyroidism with multinodular goiter. The uptake study was performed by oral administration of 4.5 – 10.0 μCi of 131I as sodium-iodide thyroid scintigraphy was performed 20 minutes after an intravenous injection of 2.0 – 4.0 mCi of 99mTc as pertechnetate. The Mean ± SD uptake values for the study subjects were found to be 36.1±15.4% ranging from 14% to 75% at 2 h and 59.9±15.9% ranging from 32% to 90% at 24 h measurements. The present results of uptake values clearly exceed the normal range (3% – 12% for 2 h; 8% – 25% for 24 h), which indicate the hyper-functioning of thyroid, and therefore, demonstrated successfully the efficient role of radioactive iodine uptake and scintigraphy to diagnose the hyperthyroidism.